Centella asiática reduz peroxidação lipídica induzida por ácido quinolínico e nitroprussiato de sódio in vitro em regiões do cérebro de rato - Marques, Naiani Ferreira (2014)
The oxidative stress is envolved in several diseases, including neurological diseases. Centella asiatica is a medicinal plant which was has long been used to treat neurological disturbances in Ayurvedic medicine. The aim of this study was to evaluate the antioxidant potencial of different extracts of C.asiatica in vitro. Were quantified by High Performance Liquid Chromatograph (HPLC) the present compounds and examined the phenolic content of the infusion and fractions: ethyl acetate, n-butanol and dichlorometane. Furthermore, the ability of C.asiatica extracts as scavenger of DPPH., as well as, the antioxidant capacity it was analyzed, through the reduction of molybdenum (VI)(Mo6+) to molybidenum (V)(Mo5+). Finally, we determined the effect of the extracts on lipid peroxidation induced by quinolinic acid (QA) and sodium nitroprusside (SNP) in different regions of the rat brain (cerebral cortex, striatum and hippocampus). HPLC analysis showed that flavonoids, triterpene glycosides, tannins and phenolic acids were present in extracts of C.asiatica. The content of phenolic compounds showed that the ethyl acetate fraction is rich in these compounds, followed by dichloromethane fraction of butanol and of infusion. Moreover, with the first analyzes it was also found a higher antioxidant potential of ethyl acetate fraction as DPPH. radical scavenger. In agreement with in vitro assays, the ethyl acetate fraction showed the highest antioxidant effect by decreasing lipid peroxidation induced by AQ in cerebral cortex (IC50 = 11.82), striatum (IC50 = 13.91) and hippocampus (IC50 = 13. 55) from rat brain. However, when the pro-oxidant agent was NPS, potency of infusion, the ethyl acetate fraction and dichloromethane were not significantly different to the cortex and hippocampus, which highlighted a greater difference of action in the striatum between the infusion (IC50 = 16.12), the ethyl acetate (IC50 = 13.57) and dichloromethane (IC50 = 11.05) regarding the butanol fraction (IC50 = 47.94). In conclusion, the results demonstrated that the infusion of C.asiatica and other fractions exhibit antioxidant capacity in vitro, which is related to their phytochemical content. Thus, the therapeutic potential in neurological diseases of C. asiatica, could be associated with its antioxidant activity.